Impact of an International Nosocomial Infection Control Consortium multidimensional approach on catheter-associated urinary tract infections in adult intensive care units in the Philippines: International Nosocomial Infection Control Consortium (INICC) findings - Josephine Anne Navoa-Ng; Regina Berba; Victor D. Rosenthal; Victoria D. Villanueva; María Corazon V. Tolentino; Glenn Angelo S. Genuino; Rafael J. Consunji; Jacinto Blas V. Mantaring, III (Elsevier, 2013)
Summary: Objectives: To assess the impact of a multidimensional infection control approach on the reduction of catheter-associated urinary tract infection (CAUTI) rates in adult intensive care units (AICUs) in two hospitals in the Philippines that are members of the International Nosocomial Infection Control Consortium. Materials and methods: This was a before-after prospective active surveillance study to determine the rates of CAUTI in 3183 patients hospitalized in 4 ICUS over 14,426 bed-days. The study was divided into baseline and intervention periods. During baseline, surveillance was performed using the definitions of the US Centers for Disease Control and Prevention and the National Healthcare Safety Network (CDC/NHSN). During intervention, we implemented a multidimensional approach that included: (1) a bundle of infection control interventions, (2) education, (3) surveillance of CAUTI rates, (4) feedback on CAUTI rates, (5) process surveillance and (6) performance feedback. We used random effects Poisson regression to account for the clustering of CAUTI rates across time. Results: We recorded 8720 urinary catheter (UC)-days: 819 at baseline and 7901 during intervention. The rate of CAUTI was 11.0 per 1000 UC-days at baseline and was decreased by 76% to 2.66 per 1000 UC-days during intervention [rate ratio [RR], 0.24; 95% confidence interval [CI], 0.11-0.53; P-value, 0.0001]. Conclusions: Our multidimensional approach was associated with a significant reduction in the CAUTI rates in the ICU setting of a limited-resource country. Keywords: Philippines, Catheter-associated urinary tract infections, Developing countries, Adult intensive care unit, Multidimensional approach, Bundle